PENYELENGGARAAN DAN PENANGANAN KESEJAHTERAAN SOSIAL GELANDANGAN DAN PENGEMIS - Utami Tuarita, Tridita Yuniar; Hernawan, Denny; Apriliyani, Neng Virly; Rusliandy; Wahyudin, Cecep; Salbiah, Euis; Ramdani, Faisal Tri; Munjin, Akhmad (Universitas Djuanda, 2024)
Targeted policies and programs that consider the needs of the community must be supported by government efforts to establish appropriate policies. Effective policies are essential for ensuring that programs can be implemented successfully. The purpose of this study is to assess the effectiveness and efficiency of the policy for handling social welfare services for the homeless and beggars at the Social Service Office of Bogor City. This research utilizes a policy implementation theory consisting of four main components: Communication, Resources, Disposition, and Bureaucratic Structure. A descriptive quantitative analysis approach is employed in this study. Data were collected through field observations and questionnaires distributed to 24 respondents. For data analysis, the Weight Mean Score (WMS) formula was used, and measurement was conducted using a Likert scale. The results indicate that the communication dimension scored 4.81, categorized as very good; the resource dimension scored 4.61, also categorized as very good; the disposition dimension scored 4.25, categorized as very good; and the bureaucratic structure dimension scored 4.65, categorized as very good. Consequently, the overall score for the policy implementation assessment was 4.58, categorized as very good. It is hoped that this research will assist the Social Service Office of Bogor City in evaluating or reconsidering the policies for handling social welfare services for the homeless and beggars in Bogor city.